Family Functioning as Perceived by Adolescents and its Relation With Social Competence and Anxiety - Alaedein , Jehad; Al-Ali, Tagreed (Jordan Journal of Educational Sciences, 2014)
The csurrent study sought to explore the interrelationships among family functioning (cohesion, adaptability), parental practices, social competence and anxiety. The study sample consisted of 378 students in seventh, eighth and ninth grades in the public schools in the governorate of Zarqa in Jordan. Results have identified a statistically significant positive relation between positive parenting practices and family healthy functioning of cohesion and adaptation. Results of multiple stepwise regression analyses show that the two factors of (a) mother's negative parenting and (b) low levels of family cohesion predicted significantly higher level of adolescents' self-ratings of anxiety; that the two factors of (a) father's positive parenting practices and (b) high levels of family cohesion predicted significantly higher level of parent' ratings of social competence. It was also found that father's positive parenting practices were the only factor that predicted significantly higher level of teachers' ratings of their students' social competence. Finally, findings showed no significant differences in the study's measures due to adolescent's gender except for anxiety scale. The study suggests that these findings could be used to design targets for therapeutic interventions and psychoeducation. counseling programs for dysfunctional families and their children